Penguatan Pengetahuan Hukum dan Peningkatan Ekonomi Keluarga Guna Pencegahan KDRT - S, Zaini Munawir; Mubarak, Ridho; Utama Nasution, Amrin Mulia (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Domestic violence (DV) remains a serious problem in Indonesian society. Many people, especially in rural areas, do not understand that domestic violence is illegal and has negative impacts on families, especially women and children. Lack of legal knowledge and limited family finances are often triggers and obstacles to preventing and addressing domestic violence. Therefore, strengthening legal knowledge and improving family finances are crucial to preventing domestic violence in the community. The main objective of this community service activity is to increase public understanding of the importance of legal protection for victims of domestic violence. Empowering family finances as a preventative measure makes families more independent and less vulnerable to domestic violence. The methods used in this community service include legal counseling through lectures, discussions, and question-and-answer sessions to provide an understanding of domestic violence and legal protection. Overall, strengthening legal knowledge and improving family finances have proven effective in preventing domestic violence and building harmonious families.